The correspondence of Erasmus. Letters 2357 to 2471, August 1530-March 1531 ([Place of publication not identified] : Univ of Toronto Pr, 2016)
Many of the letters in this volume, which covers the period August 1530 to March 1531, reflect Erasmus' anxieties over events at the Diet of Augsburg (June-November 1530).
Cover; Copyright; Contents; Illustrations; Preface; Map showing the principal places mentioned in volume 17; LETTERS 2357 to 2471; Table of Correspondents; Works Frequently Cited ; Short-Title Forms of Erasmus' Works; Corrigenda for CWE 16; Index
Print version record.
Master record variable field(s) change: 050, 072, 082, 600, 650, 651
Keywords: Erasmus, Desiderius, -- -1536 -- Correspondence; PHILOSOPHY / History & Surveys / Renaissance; Authors, Latin (Medieval and modern) -- Netherlands -- Correspondence; Netherlands -- Intellectual life -- 16th century -- Sources; Humanists -- Netherlands -- Correspondence; Electronic books